Mekanisme Atrial Fibrilasi pada Hipertiroid - Wenny Fitrina Dewi; Yoga Yuniadi (The Indonesian Heart Association, 2011)
Atrial fibrillation (AF) is the most common cardiac arrhythmia other than sinus tachycardia encountered in hyperthyroidism and representing an independent risk factor for cardiovascular event. Atrial fibrillation occurs in 10-15% of patient with hyperthyroidism, where as prevalence increase with advancing age. The heart is a major target organ for thyroid hormone action. Thyroid hormones exert their cardiovascular effects either directly at cardiomiosit through nuclear receptors (gen transcription) and extra nuclear (cellular) which is influence inotropic, chronotropic and dromotropic effect and indirectly by influencing sympatoadrenergic system and altering peripheral hemodynamic. Hyperthyroidism is associated with an increased supraventricular ectopic activity. Hyperthyroidism increases the rate of systolic depolarization and diastolic repolarization, decreases the duration of the action potential and refraction period of the atrial myocardium, as well as atrioventricular nodal therefore facilitated the occurrence of atrial fibrillation.